PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE LEARNING TOURNAMENT UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN HIDROLISIS GARAM DI KELAS XI SMA NEGERI 4 PEKANBARU - Intan Romauli; Elva Yasmi Amran; Roza Linda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This Research is about the application of active learning strategy learning tournament type that has conducted to know the increasing of student’s learning achievement on of salt hydrolysis at class XI SMAN 4 Pekanbaru. This research is experimental research with randomized control group pretest-posttest design. The sample consisted of two classes, XI IPA 2 class as experimental class and XI IPA 5 class as control class. Experimental class is a class that is used application of active learning strategy learning tournament, while the control class was not. Data analysis technique used is the t-test. Based on analysis of data obtained tarithmetic > ttable is 3,37 > 1,67, means that the application of active learning strategy learning tournament can improve student achievement on the subject of reaction rate in class XI SMAN 4 Pekanbaru where the effect of an increase is 16,34%.Keywords : Learning Achievement, Learning Strategy Learning tournament, and of Hydrolysis of salt